Percepção de pessoas idosas sobre a promoção de saúde mental em grupo de convivio na atenção primária a saúde - Morais, Kevin Fontelles (2024)
This was a descriptive and observational study, with a qualitative approach, whose research field was the Municipal Center for Senior Citizens, located in the city of Campina Grande, Paraíba, Brazil. The general objective was to identify the perception of elderly people about the experiences and potential for promoting mental health in a social group in Primary Health Care, being developed through the following specific objectives: - To evaluate the experiences of elderly people about the social group in relation to the promotion of mental health; To investigate the perceptions of elderly people about the social group as a space for promoting mental health; To describe the potentialities and/or weaknesses of the social group in relation to the promotion of mental health. The sample was made from a convenience sample, totaling thirteen people, with data collected between May and September 2024. The instruments used in data collection were: 1) Mini-Mental State Examination; 2) sociodemographic and health form of the participants; 3) interview script on the perception of elderly people about the potential of the social group in relation to the promotion of mental health in Primary Care. The analysis of subjective data was based on the Content Analysis proposed by Bardin, while the objective data were analyzed using descriptive statistics. The research followed the principles of bioethics in which equity, autonomy and justice were considered, established by Resolution No. 466 of December 12, 2012 of the National Health Council and was approved by opinion number: 6,466,247. The results of the research demonstrated a greater presence of females aged between 60 and 80 years and with some type of comorbidity. The thematic categorical analysis provided four thematic categories and one subcategory, namely: Category 1 - Social interaction as a source of well-being, and one Subcategory - Experiences in the social group and the promotion of mental health; Category 2 - The social group as a protective factor against loneliness and mental suffering in the elderly; Category 3 - The social group as a promoter of health activities; Category 4: The social group as a promoter of care and attention; and subcategory 1 - The social group as a promoter of care in normal or pathological aging. It was concluded that social groups are instruments that can assist in the process of promoting the health of the elderly, since they encourage the performance of activities, as well as the establishment of interaction and social ties that culminate in a support network capable of promoting the well-being, leisure and development of the elderly.